Model Of Digital Transformation in Banking Sector - Vebtasvili, Vebtasvili (Universitas Airlangga, 2024)
Digital transformation has become the foundation for building policy, organizational, and HR transformations. The paper estimates a model of digital transformation in banking sector reflect on the phenomenon, the literature from multiple fields, and case studies. The data is used from the case of The Financial Services Authority (OJK) and Bank Indonesia. The finding shows that the internal factors, external factors, and risks could determine whether the implementation of the digital transformation model succeeds. There are still many improvements to integrate overall and work for the digital transformation.